MINERAL ELEMENT DISTRIBUTION OF COTTON (GOSSYPIUM HIRSUTUM L.) SEEDLINGS UNDER DIFFERENT SALINITY LEVELS - (:unkn) unknown (PAKISTAN BOTANICAL SOC, 2012)
Cotton (Gossypium hirsutum L.) is the world's leading natural fiber and second largest oilseed crop. In addition to textile manufacturing, cotton and cotton-by products are the sources of wealth of consumer based products, livestock feed, fertilizer, foodstuff and paper. High concentrations of NaCl in soils account for large decreases in the yield of a wide variety of crops all over the world. The present study was conducted to evaluate NaCl stress on mineral nutrient composition of cotton due to its economic importance. Cotton seeds were germinated in Magenta vessels containing Murshige and Skoog (MS) media for 15 days and then transferred in sterile jars containing MS exposed to different levels of NaCl (50, 100, 200 and 400 mM) treatments for 1 month. Uptake of some mineral nutrients (B, Ca, Fe, K, Mg, Mn, Na and Zn) by the plants was examined in roots and leaves by using an Inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES). The data proved that plant growth and uptake and accumulation of microelements are altered extensively in cotton grown with NaCl. Excess NaCl reduces the uptake pattern of certain elements and increases that of others, the patterns depending on the element and the plant part being compared to the control.
Keywords: SALT STRESS; LIPID-PEROXIDATION; ANTIOXIDATIVE ENZYMES; POTASSIUM CHANNEL; PLASMA-MEMBRANE; SODIUM-CHLORIDE; ION CHANNELS; CALCIUM; GROWTH; TOLERANCE